Burnout and Associated Factors among Iranian Emergency Medicine Practitioners - Mohammad Jalili; Gholamreza Sadeghipour Roodsari; Anahita Bassir Nia (Tehran University of Medical Sciences, 2013)
Background: Emergency physicians are at risk of burnout, which can affect their mental health, as well as patient care. We assessed burnout level among Iranian emergency physicians and investigated demographic, work-related factors and stressors associated with higher burnout.Methods: In a cross-sectional study, we surveyed all 188 emergency medicine residents and practitioners in Iran. We measured burnout using 22-item Maslach Burnout Inventory assessing emotional exhaustion, depersonalization and personal accomplishment, also demographic factors, work related factors and sources of stress in emergency department using anonymous self-administered questionnaire. Descriptive analysis, univariate analysis to evaluate association with higher score of burnout, and multivariate logistic regression analysis to predict high burnout in 3 subscales was performed.Results: Totally, 165 questionnaires were filled (response rate: 88%; mean age: 33.6 years, 91% male). Mean burnout scores were 22.94 for emotional exhaustion (95% CI=20.78-25.01; moderate), 9.3 for depersonalization (95% CI=8.24-10.36; moderate to high), and 31.47 for personal accomplishment (95% CI=29.87-33.07; moderate to high). Frequent reported sources of stress were shortage of equipment, problem with work physical environment, and relationship with other services. All 19 sources of stress were associated with higher score of emotional exhaustion and depersonalization; while twelve out of 19 were significantly associated with lower level of personal accomplishment. In logistic regression model, the significant predictors for high emotional exhaustion were work overload, feeling of insecurity for future career and difficulties to balance professional and private life.Conclusion: Burnout is high among Iranian emergency medicine practitioners and some interventions can be proposed to reduce stress.